Effect of Supplementation of Bypass Fat on Lactation Performance in Dairy Cows - Suresh Kumar, P (The Indian Veterinary Journal, 2026)
The present study was undertaken to evaluate the influence of supplementation of bypass fat on lactation performance in crossbred cows. Twelve crossbred lactating Jersey cows were divided into two groups, viz., Group T1 (Control) and T2 (Treatment). Group T1 fed roughages and concentrate mixture as per standard practice followed in the farm, and group T2 received the same ration as group T1 and supplemented with bypass fat @ 30g/100 kg BW. The milk production, 4% FCM yield, milk fat, total solid content and specific gravity of milk were significantly (P<0.01) increased in cows in the bypass fat-supplemented group (T2) compared to the control. The bypass fat supplementation @ 30 g/100 kg body weight per day was beneficial and cost-effective in improving milk production and milk composition.